Towards the development of a model of sustainability for Paulinian mission schools - Columbano, Mary Edwardine (Animo Repository, 2001)
The purpose of this study determines the level of sustainability of low-tuition fee-based mission schools owned and managed by the St. Paul system. The methodology adopted in this study is the historical/quantitative approach. It relied heavily on the financial statements of the schools under study. Financial ratios were used to describe the various levels of financial conditions the schools under study went through including the various alternative discussions that were implemented. A field survey was used on the monthly income, family sizes and occupation of clientele's parents. The participants in this study consisted of the low tuition fee-based schools managed by the Sisters of St. Paul of Chartres, Philippine province. The results of the study revealed that the main sources of revenue of these schools were educational and other fees and other income or non-educational revenues. However, educational revenues were not sufficient to meet operating expenses, Other incomes were derived from traditional income generating noneducational activities such as the school canteen, bookstore, etc. these other income were sufficient to augment deficits incurred in operating expenses and at the same time were used to acquire capital assets.